Canonical Relations Of Sensorimotor Reactions Of Multilateral And Bilateral Body Parts - Dodig, Miroslav (Advances in Social Sciences Research Journal, 2015)
The research study was carried out on a sample of 20 subjects, of male gender, from 20 to 22 years of age. An analysis was carried out in the space of sensorimotor reactions of multilateral and bilateral (parallel, transversal, diagonal) body parts. The evaluation of sensorimotor reactions in multilateral and bilateral body structures was developed through an especially constructed instrumentarium (Kinesiometer, M. Dodig, 1987). The obtained results have been processed by application of canonical correlational analysis (Cooley and Lohnes,1971). Based on maximum cohesion between the pair of linear functions of variable groups that measured sensorimotor reactions (transversal, parallel, diagonal) body parts, a significant cohesion of latent multilateral and bilateral dimensions was obtained. This cohesion undoubtedly indicates the significance of the coherence process of separate and cooperative functions of the right and left cerebral hemisphere which can produce clearly differentiated reactions in terms of multilateral and bilateral body parts. In addition, the sensorimotor reaction is dependent on the speed of change of excitation and inhibitions of those central areals that govern execution of sensorimotor reactions. The matter at hand is sequential regulation that comprises of activation of motor units of various degrees, synergy regulation and tonus regulation which are determined according to both multilateral and bilateral structures.